THE IMPACT OF THE ESTABLISHMENT OF MODERN SHOP IN THE MIDDLE OF GROCERY SHOP (Survey on Grocery Stores in Cisaga District, Ciamis) - Rachman, Yoga Tantular; Akbar, Dendy Syaiful (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research is analyzing about solution of impact of appearance modern stores toward grocery stores at subdistrict in Ciamis. This research indicate that apprearance of modern stores and the distance between modern store and grocery store affect the change of sales turnover and profit of grocery stores. The purpose of this research is to find out solution about impact of apprearance and the distance between modern store and grocery store affect the of change of sales turnover and profit of grocery stores.This research use descriptive analysis based on data collecting by interview, observation and literature study to explain affect from apprearance and the distance between modern store and grocery store toward change of sales turnover and profit of grocery stores.Consistent with prior researches, the result based on data collecting by interview, observation and literatures study show that the grocery stores in subdistrict Ciamis can’t compete with modern stores, it showed from the decreased of sales turnover and profit in grocery stores. The average decrease of sales turnover in grocery store is 34,21%, while profit have the average decrease 35,26%. The other result show decreasing of sales turnover and profit is more significantly when the distance between grocery store and modern store between one to two kilometer.